Depression, anxiety and streee in young adult breast cancer women undergoing adjuvant therapy in HUSM - Leng, Leong Yee (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
Depression, anxiety and stress are normal psychological and emotional disturbances occurs among young adult women with breast cancer due to side effects of breast cancer treatments and alteration in physical image. Meanwhile, breast cancer continues to develop especially in countries, such as Malaysia. There is little attention paid to describe these treatment side-effects experienced by young adult breast cancer women, thus this led the researcher to undertake this study. The aims of this study was to identify the association between ages or the time after initial diagnosis and the level of depression, anxiety and stress among young adult breast cancer women. This is a descriptive study on young adult breast cancer (BC) women undergoing adjuvant therapy in Hospital University Sains Malaysia (HUSM). Data was collected by self-administered, anonymous questionnaire. A total of 21.6% (n=11) young breast cancer women undergoing adjuvant therapy experienced depression, 51% (n=25) with anxiety, and 11.8% (n=6) of the young adult breast cancer women with stress. More than 10% of young adult BC women are suffered from depression, anxiety and stress. These results suggest that young adult BC women are affected by psychological burden.